PERAN BMT BISMA PADA PEMBIAYAAN MIKRO TERHADAP PERKEMBANGAN UMKM DI CIPONDOH KOTA TANGERANG - luthfianti alfahira; mariya ulpah (Institut Binamadani Indonesia, 2026)
This study aims to determine the role of BMT Bisma Cipondoh in microfinancing towards the development of MSMEs in improving the economy of the Cipondoh community. The focus of the research is directed at how BMT provides easy access to capital, as well as its contribution in supporting the growth of small businesses and improving community welfare. The research method used is a qualitative approach. Data collection was carried out through interviews and observations. Interviews were conducted with parties from BMT Bisma and BMT Bisma customers, observations were conducted by visiting business p remises managed by BMT BISMA customers. The results of the study show that BMT BISMA not only plays a role as a capital provider, but also as a business coach and companion through simple financial training, marketing strategies, and guidance on solving business problems. The financing process at BMT is simpler and more flexible than formal financial institutions, thus providing convenience for MSME actors. The positive impacts felt by customers include increased family income, fulfillment of daily needs, children's education costs, and the creation of saving habits. In addition, the growing business also creates new jobs, helps reduce unemployment, and strengthens the local economy through the circulation of money within the Cipondoh community. The conclusion of this study is that BMT BISMA Cipondoh plays a crucial role in helping small businesses grow. BMT not only provides capital loans but also guides and assists entrepreneurs to achieve better direction. Consequently, businesses can grow, customers' families become more prosperous, new job opportunities are created, and the Cipondoh community's economy becomes more prosperous.